2016
DOI: 10.1242/dev.129775
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative analysis of growth control in theDrosophilaeye disc

Abstract: The size and shape of organs is species specific, and even in species in which organ size is strongly influenced by environmental cues, such as nutrition or temperature, it follows defined rules. Therefore, mechanisms must exist to ensure a tight control of organ size within a given species, while being flexible enough to allow for the evolution of different organ sizes in different species. We combined computational modeling and quantitative measurements to analyze growth control in the Drosophila eye disc. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
62
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(66 citation statements)
references
References 40 publications
4
62
0
Order By: Relevance
“…According to an alternative model, uniformly declining growth results from a combination of Dpp signaling and mechanical feedbacks12153233. Finally, we have recently shown that the growth rate of the apical area in the Drosophila eye imaginal disc declines inversely proportional to the total apical area, which is consistent with a dilution-based mechanism for growth control34.…”
supporting
confidence: 69%
See 3 more Smart Citations
“…According to an alternative model, uniformly declining growth results from a combination of Dpp signaling and mechanical feedbacks12153233. Finally, we have recently shown that the growth rate of the apical area in the Drosophila eye imaginal disc declines inversely proportional to the total apical area, which is consistent with a dilution-based mechanism for growth control34.…”
supporting
confidence: 69%
“…We have previously shown that the declining area growth rate in the eye disc can be described by an area-dependent decline34 of the form…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Pupal wing discs were dissected at 30 and 48 hours post puparium formation. Staining and confocal imaging was carried out as described [26].…”
Section: Imaging Of Tissue Samplesmentioning
confidence: 99%